Faktor-Faktor Yang Mempengaruhi Pemanfaatan Posbindu PTM pada Masa Pandemi COVID-19 di Puskesmas Dalu Sepuluh Kecamatan Tanjung Morawa - Siti Zulkhairani; Fitriani Pramita Gurning (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Non-communicable diseases have become the main cause of death globally and nationally, due to the high number of PTM which continues to increase every year, so to control PTM risk factors in Indonesia, the government has established the PTM Posbindu program. However, the utilization of PTM Posbindu in the working area of ​​Dalu Ten Health Center has not reached the 100% target. This study aims to determine the factors that influence the use of PTM Posbindu during the COVID-19 Pandemic in the Dalu Ten Health Center working area. This type of research is quantitative with a cross-sectional design. The population in this study is people aged 15-59 years in the working area of ​​Dalu Ten Health Center. The sample in this study amounted to 96 people. The sampling technique used stratified random sampling. Data analysis used univariate, bivariate, and multivariate analysis. The results showed that 80.2% of the 96 respondents used Posbindu PTM. Variables that influence the utilization of PTM Posbindu are supported from health workers (p=0.001), mileage variable (p=0.001), family support (p=0.001), knowledge (p=0.005), and support from health cadres (p=0.005). The variable that did not affect the utilization of PTM Posbindu was the health status variable (p=0.305). The results of the multivariate analysis of the most dominant variables were the support of health workers (p = 0.001 <0.05 and the value of Exp (β) or OR = 11.318). The conclusion of this study is that the most influential variable is the support of health workers with 11 times greater use of PTM Posbindu during the COVID-19 Pandemic. It is recommended for health workers be able to provide other innovations in Posbindu activities to attract public interest in visiting PTM Posbindu during the current COVID-19 Pandemic.